SHVOT AND ISHVUT: A COMPARATIVE ANALYSIS OF ARMENIAN LOWER MYTHOLOGICAL CHARACTERS - Галстян, Асмик Г.; Чолакян, Акоп М. (History, Archeology and Ethnography of the Caucasus, 2025)
This article examines Shvot or Ishvut, an evil spirit well-known in Armenian lower mythology and folk beliefs. Drawing on ethnographic materials collected from various regions of Armenia and among Armenian communities in the Kessab region of Syria, the study employs primarily historical methods, including historical-comparative and chronological approaches, alongside specialized ethnographic methods such as in-depth qualitative analysis. The research delineates the defining characteristics, functions, manifestations, and associated attributes of Shvot. The primary objective is to analyze this lower mythological figure through a synchronic approach, utilizing folklore and ethnographic sources documented from the mid-19th century to the present. Etymological considerations, name verification, and related issues are addressed peripherally using an asynchronous approach with historical sources, though these remain secondary to the study’s main focus. Shvot is identified as a calendar spirit, predominantly associated with the Terendez holiday and the New Year. According to folk beliefs, the Shvot spirits reside in human dwellings during winter and are expelled through specialized exorcism rituals at the onset of spring, rituals that symbolically reflect the transition from winter to spring. The name Shvot exhibits phonetic variations across Armenian dialects, yet its functions remain consistent. The spirit is believed to inhabit homes, barns, and storerooms during winter, consuming food stored in barns, harming livestock, and deceiving women as an untrustworthy entity. Shvot is situated within a broader spectrum of spirits in Armenian lower mythology, and its parallels within the Armenian belief system are explored in detail in this study.